PENERAPAN MEDIA BOARD GAMES UNTUK KEMAMPUAN NUMERASI SISWA PADA OPERASI HITUNG PENJUMLAHAN DI SEKOLAH DASAR - Viadana Yuli Prasisca; Dian Permatasari Kusuma Dayu; Rosniwaty; Himmatul Khoiroh; Siti Qomariyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Basic skills that students must have when they are in elementary school are reading, writing and arithmetic. In basic arithmetic skills, students must be able to master addition skills and number values. The purpose of this study was to improve students' numeracy skills in summative arithmetic operations. This research method uses PTK implemented at SDN Gading 5 Surabaya. The use of Board game media can improve students' addition and place value skills for grade II Elementary School students. This Classroom Action Research (PTK) was conducted at SD Negeri Gading V Surabaya in the odd semester of the 2024/2025 school year. The subjects in this study were grade II C students, consisting of 39 students, namely 17 male and 22 female students. The object of the study was board game media in Mathematics. The researcher carried out 5 learning cycles consisting of pre-cycles and 4 daily cycles. The implementation of Classroom Action Research was carried out in each cycle, including: planning, implementing actions, observation, and reflection. The instruments used in this study were initial test questions and final test questions. The results of the study in each cycle showed an increase in learning outcomes from the pre-cycle to the fourth cycle. Each group gave satisfactory final results. In the Pre-Cycle, the percentage of student learning completion reached 56%, in Cycle I it reached 69%, in Cycle II it reached 74%, in Cycle III it reached 79%, in Cycle IV it reached 92%. In conclusion, the application of board games media improved students' abilities, understanding and motivation in learning Mathematics, especially in the ability to add and determine the place value of numbers.